2010
DOI: 10.5367/000000010792278400
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships among Korean Outbound Tourism Demand: Granger Causality Analysis

Abstract: This study investigates Korean outbound tourism demand and its determinants using the Granger causality (GC) analysis. In contrast to previous studies, which deal only with internal factors such as exchange rate and income, this study examines the effects of interactions among countries and, therefore, produces more complete and relevant results. Korean outbound tourism to the USA is causally related to Korean outbound tourism to the other six countries in the study. These results can be used in tourism market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…These studies often firstly confirm the co-movements of tourism demand in different destinations using the co-integration technique and then use VAR models to test for the cause-effect relationships among these demand variables of the destinations under consideration via the Granger causality test (Granger, 1969). Torraleja et al (2009) and Seo, Park, and Boo (2010) identify the existence of causal relationships between the tourism demand variables across different destinations. In particular, Seo, Park, and Yu (2009) recognise the time varying rather than the constant conditional correlations in their study and examine the determinants of conditional correlations among destinations using the VAR model.…”
Section: Interdependence and Interrelationmentioning
confidence: 99%
“…These studies often firstly confirm the co-movements of tourism demand in different destinations using the co-integration technique and then use VAR models to test for the cause-effect relationships among these demand variables of the destinations under consideration via the Granger causality test (Granger, 1969). Torraleja et al (2009) and Seo, Park, and Boo (2010) identify the existence of causal relationships between the tourism demand variables across different destinations. In particular, Seo, Park, and Yu (2009) recognise the time varying rather than the constant conditional correlations in their study and examine the determinants of conditional correlations among destinations using the VAR model.…”
Section: Interdependence and Interrelationmentioning
confidence: 99%
“…In the tourism sector this can result in demand co-moving across borders, which can be affected by idiosyncratic shocks in other countries/regions such as economic instability, natural disasters, and sociopolitical upheavals (Word Travel and Tourism Council 2011). Seo, Park, and Boo (2010) and Torraleja, Vázquez, and Franco (2009) have addressed the interrelationships between factors that drive demand for tourism in different destinations using VAR models. A destination's demand, as a significant part of international service trading, can also affect the local economy, which further generates spill-over effects on other economies (Nowak, Sahli, and Cortes-Jimenez 2007;Schubert, Brida, and Risso 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their review of tourism economics research, Song et al () suggested that more research effort should be put on modelling the interrelationships among international tourism demand through a more complete system that captures the endogeneity among the economic variables. While many studies analysed the relationships of tourism demand and economic variables (e.g., income and price), only a few studies addressed the interrelationships of tourism demand among different destinations (Seo, Park, & Boo, ). Nevertheless, this has become an emerging topic in recent tourism demand literature (Song et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seo, Park, and Yu () investigated the determinants of the relationship among Korean outbound tourism demand for Jeju Island and three other Asian island countries: the Philippines, Singapore, and Thailand, finding indications that these countries are substitutes for the Jeju Island. Furthermore, Seo et al () analysed the multidirectional causal relationships of the Korean outbound tourism demand across seven destination countries. Their results indicated that Korean outbound tourism for the United States directly causes Korean outbound tourism for the other six countries.…”
Section: Literature Reviewmentioning
confidence: 99%